The Students' Perception on Using YouTube Channel "Learn English with Jessica" in Learning Speaking - Hayuningsari, Anastasya Wilujeng; W, Sri Surachmi; Rusiana, Rusiana (Prominent, 2025)
YouTube channel are helpful for students, offering videos, tutorials, and helpful content to make learning easier and explain difficult topics, like “Learn English with Jessica”. This study aimed to describe the students’ perception on using YouTube Channel “Learn English with Jessica” in learning speaking. The method used in this study is qualitative. The questionnaire and focus group discussion were conducted with 29 eleventh-grade students from the Beauty and Spa class at SMK PGRI 1 Mejobo, Kudus. The findings showed that students have a positive attitude toward the YouTube channel “Learn English with Jessica,” as it helps improve their speaking skills. The findings align with research showing that YouTube enhances pronunciation, fluency, and confidence. Students also rely on the channel for homework and exam preparation.  Students prefer the YouTube channel over traditional textbooks because of their visual and interactive nature, which keeps them engaged. For beauty and spa students, the content is particularly valuable in helping them explain treatments and communicate with customers effectively, supporting studies on multimedia's benefits for learning. The channel is also a helpful tool for self-study, with students watching videos both in and outside the classroom. This flexibility allows them to review lessons and practice speaking skills at their own pace. Furthermore, it supports homework by providing extra explanations and examples to complement classroom learning.